The Effects of Naltrexone Among Alcohol Non-Abstainers: Results from the COMBINE Study - Ray, Lara; Krull, Jennifer L.; Leggio, Lorenzo (Frontiers in Psychiatry, 2010)
These analyses of the COMBINE Study examined the effects of naltrexone among non-abstainers. Given that one of the most well-established mechanisms of action of naltrexone involves blunting of alcohol reward, it is hypothesized that naltrexone should be more effective among individuals who drank during treatment. Participants were 952 (78% of the total COMBINE Study sample) treatment-seeking alcohol dependent men and women who received pharmacotherapy for alcoholism and drank at least once during the 16-week trial. Mixed model analyses revealed that individuals who drank more regularly during the trial seemed to benefit most from naltrexone and the effects of naltrexone on heavy drinking was significant in treatment months 2 through 4 among individuals who reported drinking on 81, 68, and 60% or more of days, respectively. Those drinking frequencies were observed in 11, 15, and 19% of the sample. Similar effects were not observed for drinks per drinking day. These results suggest that a small subgroup of non-abstainers, composed primarily of very regular drinkers, appears to benefit from naltrexone in reducing heavy drinking days. Naltrexone may be effective in the context of controlled drinking approaches, even among very frequent drinkers.